An example of genre shift in the medicinal product information genre system - Ezpeleta Piorno, Pilar (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Medical writers and translators need information of three kinds: conceptual, contextual and textual. When in possession of this information, they can progressively improve their efficiency. Textual genre has proved to be useful to linguistic mediators of professional texts, providing them with the communicative and textual competence required. I suggest that the scope of textual genre can usefully be widened to include the notion of genre systems. This notion can be particularly useful for obtaining contextual information and understanding complex communicative activities in professional groups and can help enhance the professional competence of medical writers and translators. This paper has a two-fold objective: to describe the dynamic continuum of medical communication that operates in the genre system constituted by product information genres in the pharmaceutical sector also considering the restraints, genre conventions and sequence imposed by metagenres; and to illustrate the intralinguistic genre shift translation process that takes place between the summary of product characteristics and the package leaflet.